Magnetic anisotropy in the ferromagnetic insulating state of La1-x Cax Mn O3 - V. Likodimos; Pissas, M. (Physical Review B - Condensed Matter and Materials Physics, 2006)
Ferromagnetic resonance (FMR) has been applied to study the variation of magnetic anisotropy and phase separation tendencies in the ferromagnetic insulating state of stoichiometric hole-doped La1-x Cax Mn O3 (0.125≤x≤0.19). A strongly anisotropic ferromagnetic phase is identified in the ferromagnetic insulating regime. The magnetic anisotropy evolves from positive uniaxial at x=0.125 and 0.15 to negative cubiclike at x=0.175 with increasing magnitude, whereas it decreases appreciably at x=0.19, which is close to the ferromagnetic metallic phase boundary. Minor contributions from ferromagnetic inhomogeneities characterized by weaker magnetic anisotropy are traced at low temperatures for x=0.125 and 0.15, while their temperature dependence implies coupling with the major anisotropic phase. A growing tendency towards the formation of spatially separate ferromagnetic regions in the paramagnetic regime is observed at x≥0.175, as the ferromagnetic metallic phase is approached. Persistent anomalies in the temperature dependence of the FMR parameters are traced concurrently with the structural transformation at 60-70 K. © 2006 The American Physical Society.